Organizational and didactic bases of educational activity of future social pedagogues in higher education (Pedagogy of Higher and Secondary Education, 2011)
The author describes the organizational and didactic framework of training activities at the university. The mechanism of socio-pedagogical influence on future professionals, the functions of higher education in the training of future social workers.
Keywords: social worker; university; management of educational process